2011
DOI: 10.3846/13923730.2011.598337
|View full text |Cite
|
Sign up to set email alerts
|

Bidding Decision Making for Construction Company Using a Multi-Criteria Prospect Model / Statybos Įmonės Apsisprendimas Dalyvauti Konkurse Naudojant Daugiakriterinį Perspektyvų Modelį

Abstract: Two critical decisions faced by bidders in competitive bidding include, firstly, whether or not to submit a bid, and secondly (if the answer to the first is ‘yes’) what markup value should be used on the submitted bid. In the construction industry, government agencies and private sector clients typically adopt competitive bidding to determine contract awards. Contractors also apply the same approach to bidding decisions. There are many variables that affect contractor decisions regarding whether to bid and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(21 citation statements)
references
References 50 publications
0
20
0
1
Order By: Relevance
“…Cheng et al (2011) applied Fuzzy Preference Relations (FPR) and Cumulative Prospect Theory into bidding decision for construction company which is different from our paper, because we consider three situations that a bidder would encounter. Armantier and Treich (2009) interpreted overbidding in first-price auctions using probability weighting function.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Cheng et al (2011) applied Fuzzy Preference Relations (FPR) and Cumulative Prospect Theory into bidding decision for construction company which is different from our paper, because we consider three situations that a bidder would encounter. Armantier and Treich (2009) interpreted overbidding in first-price auctions using probability weighting function.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The influential factors for construction company bidding decision have been studied by many researchers (Cheng et al 2011). Cheng et al (2011) gave a summary of 44 factors identified in the literature as affecting bid/no bid decision making for construction companies. And these factors were incorporated into a questionnaire and sent to the bidders.…”
Section: Identifying the Key Influential Factors In Land Bidding Decimentioning
confidence: 99%
See 2 more Smart Citations
“…To further investigate the rationales behind markup decision of the contractors for different types of projects, Ye et al (2014) identified three main decision factors of markup: i) project nature; ii) client characteristic; and iii) market environment. Cheng et al (2011) integrated various approaches, including fuzzy preference relations, multi-criteria prospect model and cumulative prospect theory to develop a bidding decision model and provide optimal markup scale advices to contractors. Despite these efforts, a couple of issues remains unsolved in the construction industry: 1) Does it mean that contractors have no need to participate in the formulation of competitive bidding?…”
Section: A Contractor Perspectivementioning
confidence: 99%